Safety of Performing a Graded Exercise Test Early after Stroke and Transient Ischemic Attack. Issue 5 (27th November 2019) - Johnson, Liam; Kramer, Sharon F.; Catanzariti, Gabriella; Kaffenberger, Tina; Cumming, Toby; Bernhardt, Julie
Abstract : Background: Low cardiorespiratory fitness (CRF) is a predictor of stroke risk and poor outcome poststroke. Fitness levels are rarely assessed in the acute phase and it is unclear if it is safe for stroke survivors and people with transient ischemic attack (TIA) to perform a graded exercise test to assess fitness. Objective: To determine if people within 14 days post stroke can safely perform a graded exercise test. Design: Observational study. Setting: Research institute. Participants: People with stroke or TIA admitted to an acute stroke unit. Intervention: Not applicable. Main Outcome Measures: Safety of performing a graded exercise test early post stroke. Safety outcomes were (1) occurrence of an adverse event or (2) <85% blood oxygen saturation (SpO2 ). Participants performed a graded exercise test on a recumbent stepper at a research institute <2 weeks postevent. CRF was determined by measuring peak volume of oxygen uptake (VO2peak ) using a metabolic cart. Results: Twenty‐nine participants were enrolled in the study (median age 69 years; interquartile range 58‐75). Sixteen were diagnosed with TIA and 13 with a mild stroke. Twenty‐eight participants completed the test; one participant was unable to perform the test due to back pain. The test was terminated due to standardized stopping criteria in 26 cases (5 = volitional fatigue, 6 = unable to keep required cadence, 15 = reaching 85% HRmax ), one due to safety (ie, SpO2 < 85%), and one was inadvertently terminated before stopping criteria were reached. Average CRF determined by the exercise test was low; mean VO2peak of 16.2 ± 4.5 mL/kg/min for men (n = 20) and 12.4 ± 3.6 mL/kg/min for women (n = 8). Conclusions: Determining exercise capacity early post stroke and TIA using a graded exercise test appears to be safe in patients with mild deficits. This information should be useful to plan tailored exercise programs. Further research should focus on determining safety of exercise testing in more severely affected stroke survivors.